PELATIHAN PENGOLAHAN DATA PENELITIAN BERBASIS SOFTWARE STATISTIK UNTUK MAHASISWA di JABOTABEK - Daryati, Daryati; Arthur, Riyan; Miharja, Tommy Eka; Ishak, Nasaruddin; Rochimah, Nur (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This service is carried out on the basis of statistics which is considered a difficult science because there are many formulas that require accuracy and precision in their calculations. As well as the many problems of students' inability to access data processing software caused by the low level of literacy in students. This service is a training activity for data processing research based on statistical software that aims to improve the quality of human resources through the ability of students to process research data. The partners of this service are universities around BODETABEK with a focus on training activities on statistical software-based data analysis techniques such as SPSS and JASP for final year students at BODETABEK. The methods used in this training activity include lectures, discussions, questions and answers, direct demonstrations and assignments. These methods were developed according to the current situation and conditions. The target to be achieved in the implementation of this activity is to improve the ability of students to carry out data analysis with the help of software such as SPSS and JASP. In addition, as an output, coaching participants are expected to be able to use SPSS and JASP software in thesis and research which can then be uploaded